Eksperimen Pembelajaran Matematika Dengan Model Pembelajaran Means Ends Analysis (MEA) Terhadap Hasil Belajar Siswa Ditinjau Dari Kemampuan Pemecahan Masalah Siswa Kelas 8 Semester 2 SMP Negeri 3 Colomadu Tahun Ajaran 2015/ 2016 - Nastiti, Kartika Ayu; , Rita P. Khotimah, S. Si., M. Sc (2016)
The purpose of research this are: (1) to examine the nfluence of learning models Means Ends Analysis toward mathematic learning outcomes. (2) to examine the influence of problem solving skills toward mathematic learning utcomes. (3) to examine the interaction between learning model and problem solving skills toward mathematic learning outcomes. The type of the research is quantitative research with quasi experimental design. The population of the research is all of student eight grade at SMP Negeri 3 Colomadu, the sample of research is VIIIA and VIIIB graders. The technique of collecting data with methods of testing and documentation. The technique of analyzing data by using the unbalanced two-way analysis of variance. The finding of the research with α = 5%: (1) there is influence of learning model Means Ends Analysis toward mathematic learning outcomes, (2) there is influence of problem solving skills toward mathematic learning outcomes, (3) there is no effect interaction between learning strategy and problem solving skills.